MUSYKILATU AT-THULLAAB FII TA'LIIM AL-IMLA` ‘ALAA THULLAABI AS-SHAFI AS-SAABI' FII AL-MADRASAH AT-TSANAWIYYAH BI MA'HAD UMMUL QURO AL-ISLAMI BOGOR (DIRAASAH HAALAH: MAUDHU’I AL-IMLA`) - Salma Fauziyyah; Asriani (Program Studi Pendidikan Bahasa Arab, 2021)
The Arabic language is one of the foreign languages that society recently occupied to study and study it, both of which are directed towards the normative and spiritual approach through the belief that the Arabic language is a religious language because the Qur’an was revealed in the Arabic language, as well as through an educational and consumer approach. Whoever believes that the Arabic language is a language that deserves to be studied deeply in order to find out about its historical and aesthetic studies. This study aims to identify the various problems facing learning the Arabic language. These problems will be analyzed so that they can be improved and solutions found to overcome them in the future This research is a qualitative research that uses data collection techniques in the form of observation, interviews, and documentation. The problems faced by seventh grade students at Umm Al-Qura Islamic Institute, which are often faced by Emla teachers, is the educational background of the students. Some students did not memorize the alphabets. To like learning Arabic, it is necessary for them to be more active in getting used to writing Arabic